Analysis by temperature-programmed reduction of the catalytic system Ni-Mo-Pd/Al2O3. (15th February 2023) - Pedroarena, Ivan; Grande, Lucía; Torrez-Herera, Jonathan J.; Korili, Sophia A.; Gil, Antonio
Graphical abstract: Characterization by temperature-programmed reduction (TPR) Highlights: Alumina-supported nickel catalysts characterized by temperature programmed reduction. The interactions between the support and the metals have been studied. Several Ni-Pd and Ni-Mo bimetallic and various Ni-Mo-Pd trimetallic catalysts have been analyzed. The order of nickel impregnation is decisive in the reducing properties. Abstract: Alumina-supported nickel catalysts are used to facilitate many reactions at various scales. However, the deactivation of these catalysts is an important problem that has prompted the search for solutions such as the addition of other metals that act as promoters. In this research, the interactions that form between the support and the metals have been studied, a fundamental property that directly affects the performance of the catalyst. With this idea, several Ni-Pd and Ni-Mo bimetallic and various Ni-Mo-Pd trimetallic samples have been prepared, and the reduction capacity of the oxide phases by temperatura-programmed reduction has been analyzed and studied. It has been found that in bimetallic catalysts, Pd favors the appearance of NiO species that are more easily reducible than Mo. In the same way, the data obtained from the trimetallic simples suggest that the impregnation order of Mo and Pd is not a determining factor in these catalysts. In addition, it has been found that the co-impregnation of Ni with Pd gives better results than the sequential impregnation of these metals. The results obtained have also shown that the order of nickel impregnation is decisive. In the case of Ni-Mo catalysts, by impregnating the molybdenum first, catalysts with better reducing properties can be obtained.